การพัฒนาโปรแกรมคอมพิวเตอร์สำหรับการวิเคราะห์อภิมานตามแนวคิดของกลาส - พัชรินทร์ แซ่แฮ่ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The purpose of this research was to develop the computer program for meta-analysis based on Glass s approach. The research and the program development had been processed to problems definition, problems analysis, computer program design, computer language selection and program writing, testing of program functioning and improving program, document for program using, and evaluate the efficiency of the program. This computer program was written by using Macromedia Dreamweaver 4.0 and Visual Basic 6.0, and was evaluated program efficiency by the researcher and 20 users who have got experience or knowledge of meta-analysis. The result of the research is created into the computer package program which contains 2 parts; 1) The handbook of meta-analysis, this part describe concept of the research synthesis and meta-analysis. 2) The meta-analysis program, which is able to receive data in 16 required form for standard index calculation, estimate standard index through by 10 direct calculation models and estimate standard index through 6 test statistic models, and also is able to receive unlimited research characteristic data. According to the efficiency evaluated by the researcher and 20 users, it is found that the program achieves to the accuracy, the reliability, protection system towards mistakes and speed. Moreover, the program is found for its up to date, easy to access, and useful for the meta-analysis research.